Building sustainable and scalable peer-based programming: promising approaches from TESFA in Ethiopia - Pari Chowdhary; Feven Tassaw Mekuria; Dagmawit Tewahido; Hanna Gulema; Ryan Derni; Jeffrey Edmeades (BMC, 2022)
Plain Language Summary In Ethiopia, married girls are a particularly vulnerable adolescent population because of the many health risks associated with early marriage. Peer-based approaches are a common strategy to improve sexual and reproductive health knowledge and behaviours for marginalized groups. Critiques of these approaches are that they lack sustainability without ongoing investment and have no lasting impact on health behaviours. CARE's TESFA programme, a peer-based approach with married adolescent girls in South Gondar, was found to be effective in creating long-term behavior change related to uptake of family planning and rates of institutional delivery. Some 88% of groups who received the TESFA curriculum were still meeting 4 years after the programme had concluded. Some participants even created groups of their own, scaling TESFA beyond the original audience, suggesting a potential approach to wider scale-up. To explore lessons learned around scale and sustainability, this study interviewed TESFA participants and stakeholders. Improvements in behaviours related to contraceptive use, institutional delivery, and girls' agency in reproductive decision-making were sustained over time regardless of group status. Factors that affected the sustainability and scale-up of groups included solidarity among group members, support from husbands and community members, ongoing savings and loan structures, flexibility of group processes, and availability of relevant curriculum topics. Through an analysis of these findings, this paper discusses recommendations for sustainable and scalable peer-based programme design via existing Ethiopian community structures. Using TESFA principles as a model, practitioners could design and implement scalable and sustainable peer-based programming for adolescents sexual and reproductive health.